Union with Christ: The Existential Nerve of Puritan Piety - Jones, R. Tudur (Tyndale bulletin, 1990)
Evidence is presented suggesting that both the experience and the doctrine of union with Christ were fundamental to the Christianity of those Puritan theologians who adhered to orthodox Calvinism.